Exploring the Impact of Fear of Missing Out (FOMO) on Impulse Purchases of JKT48 Theatre Show Tickets - Attalarik Nurravli Sadhat, Muhammad; Sisilia, Kristina (The International Journal of Business Review (The Jobs Review), 2023)
An individual with a constant Fear of Mission Out (FoMo) all updated information from his or her idols can make them do something impulsively. FOMO is a sudden feeling and desire to immediately fulfill a fan's desires and anxieties to keep up with the latest news and information of JKT48 idol artists compared to other people so that they buy expensive JKT48 theater performance tickets without any planning or known as impulse buying. This study aims to determine the effect of Fear of Missing Out (FoMo) on JKT48 fans or supporters' impulse buying behavior of JKT48 artists' theater performance tickets. With purposive sampling, data were collected from 110 respondents, namely JKT48 fans. Quantitative analysis techniques were used to examine a total of 17 questionnaires. The results show that FoMo has a significant effect, with a coefficient of determination of 37.6% of the influence of FoMo on these fans' impulse buying of show tickets. The findings of this study suggest that FoMo tends to affect the impulse buying of JKT48 fans. This result can be considered in consumer decision-making factors for the service industry in the world of artists and fans so that artist management companies can develop their business strategies.